Dose Remittances Matter for Openness and Financial Stability: Evidence From Least Developed Economies - Miao, Meng; Qamruzzaman, Md. (Frontiers in Psychology, 2021)
The study's motivation is to gauge the effects of remittances on openness: financial and economic openness and financial stability in least developed countries (LDCs) for the period spanning 1975–2018. The study applies Generalized Moment of Methods (GMM) and System-GMM to detect the magnitude of remittances, gross capital formation, and government debt on openness and financial stability, and their directional association is established by performing a Granger causality test with System-GMM specification. The results of cross-sectional dependency ascertain the presence of a common dynamic among the research units; on the other hand, both first, and second-generation unit root tests establish that variables are integrated either at level or after the first difference, neither variables are exposed to order of integration after second difference. A panel co-integration test based on error correction confirms the availability of the long-run association among variables. Study findings with GMM and System-GMM estimation expose positive statistically significant effects of remittance inflows to economic and financial openness and financial stability. In LDCs, remittance inflows positively augment economic and financial openness; moreover, financial stability remittances play a critical role. The study implemented the Granger causality test with System-GMM specification, and results disclosed the feedback hypothesis that is bidirectional causality availability in the tested empirical causal model. JEL Classifications: F24, F43, P34.